Okun’s law, FDI, and economic structure on unemployment in ASEAN countries - Yongkiki Alexander; Irsad Lubis (International Journal of Applied Finance and Business Studies, 2025)
This study aims to analyze the effect of economic growth on unemployment rates in ASEAN countries using Okun's Law and incorporating control variables of Foreign Direct Investment (FDI) and economic structure consisting of industry value added and service value added. The data used is panel data from 8 ASEAN countries over several years obtained from the World Bank. The results show that economic growth has a negative relationship with the unemployment rate, thus supporting the validity of Okun's Law in the ASEAN region. The FDI control variable shows varying effects between countries, but in general, FDI is not always able to significantly reduce unemployment. Meanwhile, the economic structure shows that an increase in the contribution of the industrial sector tends to be associated with a decrease in unemployment, while an increase in the contribution of the service sector has an effect that depends on the economic characteristics of each country. These findings confirm that stable economic growth and the strengthening of productive sectors are important factors in reducing unemployment in ASEAN. This study has implications for the governments of ASEAN countries to strengthen their industrialization strategies, increase job creation, and direct foreign investment flows to labor-intensive sectors.